A Arte Polissêmica de José Fortuna: da música sertaneja ao teatro circense (1948-1983) - Gutemberg, Jaqueline Souza (2018)
This work has as theme the artistic trajectory of José Fortuna towards the recognition in the sertaneja musical scene between the years of 1948 and 1983. Successful composer, recognized among the peers and by the public, José Fortuna figures to the present day as a poet. His work, versatile and polysemic, found resonance in the record production of his time by the most renowned performers. In order to establish this composer image, José Fortuna constructed a representation of himself as a poet, writer, playwright, entrepreneur and cultural producer, which allowed him to create and control his production, based on the conditions and interests of his time. From the 1950s onwards, with the inclusion of sertaneja music in the market and in the mass media, not all the artists composed the casting of the great record companies. Faced with such a "scheme", to remain in the sertaneja music market did not depend only on the skills or gift for music and the arts. It was necessary to know how to play, to negotiate and to shrewdly, to recreate one's acting space (or to act in others, like the circus theater), in search of recognition and greater autonomy. In this trajectory, José Fortuna creatively took advantage of the gaps in this network of music production as a business / product and took the reins of his career aiming to dictate his own rules of production, recording and circulation of his works to project himself as a composer in the Brazilian recording scene.